2017
DOI: 10.1111/micc.12386
|View full text |Cite
|
Sign up to set email alerts
|

Differences in optic nerve head microcirculation between evening and morning in patients with coronary artery disease

Abstract: Ocular microcirculation obtained from LSFG may provide a window for detecting changes in microvasculature related to CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Our previous study revealed that the average MBR-Tissue and average MBR-All values obtained by a morning evaluation in patients with coronary artery disease were significantly lower than those of patients without coronary artery disease 11 . It has also been clarified that in patients with diabetes mellitus, intima-media thickening shown by ultrasonography reflects a decrease in the average values of all sections of the MBR in the ONH 12 .…”
Section: Discussionmentioning
confidence: 86%
“…Our previous study revealed that the average MBR-Tissue and average MBR-All values obtained by a morning evaluation in patients with coronary artery disease were significantly lower than those of patients without coronary artery disease 11 . It has also been clarified that in patients with diabetes mellitus, intima-media thickening shown by ultrasonography reflects a decrease in the average values of all sections of the MBR in the ONH 12 .…”
Section: Discussionmentioning
confidence: 86%